The role of recreational sports activity in achieving psychological well-being for the mentally disabled - Rahli, Mourad; Lournik, Youcef (sports creativity, 2025)
The process of caring for the mentally disabled has gone through several stages, as mentioned by Mohamed Mekdad (2007) in his presentation entitled "Preparing Teachers of Regular Students to Care for People with Special Needs in Light of Inclusion Methods." The first stage was one of neglect and exclusion, predating the advent of monotheistic religions. The Greeks, Romans, and Byzantines advocated for their removal from society, believing they were harmful and should be banished and deprived of all rights and obligations. This was followed by a stage of care and attention, as monotheistic religions called for their well-being. Christianity, for example, considered caring for them out of compassion and mercy to be among its duties. The third stage saw a return to neglect and exclusion from the 15th century to the 19th century. The fourth stage was one of isolation, beginning in the 18th century and continuing until the mid-20th century. The stage of educational integration lasted from the mid-20th century to the end of the 20th century. Finally, the stage of comprehensive integration began at the start of the 21st century, aiming to achieve psychological well-being and allowing us to judge the progress of society. The old view held that this group was the benchmark by which society was measured.